Pengaruh Penggunaan Media Audiovisual Dan Model Pembelajaran Team quiz Terhadap Hasil Belajar IPA - Dian Perayanti Sinaga; Sumarny Tridelpina Purba; Nanda Winalda (Journal of Natural Sciences, 2022)
This study aims to determine the effect of using audiovisual media and the team quiz learning model on learning outcomes. The sampling technique used cluster random sampling with experimental sample I (MIPA2) using audiovisual media and experiment II (MIPA3) using the team quiz learning model. The instrument used a multiple choice test of 20 questions and then analyzed to find the mean, median, mode, standard deviation, normality test, homogeneity, linearity, paired sample t-test, independent sample t-test, regression test, t-test, f-test, the coefficient of determination test, and the category of learning outcomes. Furthermore, the data obtained were analyzed using the ANOVA test with a significance level of 5% (α = 0.05) with the help of the SPSS 21 program. The results showed a significant effect between the use of audiovisual media and the team quiz learning model on learning success with a probability value of 0.000 = 0.05 with Fhitung 16.581 FTable 4.006. The results of the paired sample t-test showed that there was a 17.33% difference between the use of audiovisual media and the team quiz learning model. Thus Ha is accepted and H0 is rejected, which means that the use of audiovisual media and the team quiz learning model affects learning outcomes at SMA YPK Pematangsiantar.